CRP and IL-6 levels of gingival crevicular fluid in stroke survivors: A pilot study / Normaliza Ab. Malik … [et al.] - Ab. Malik, Normaliza; Mohamad Yatim, Sa’ari; Jin, Lijian; McGrath, Colman (Universiti Teknologi MARA Cawangan Selangor, 2019)
Introduction: The aim of this study was to evaluate the levels of C-reactive protein (CRP) and interleukin-6 (IL-6) in the gingival crevicular fluid (GCF) among stroke survivors in relation to the oral hygiene status and stroke characteristics. Methods: A multi-centre cross-sectional study was conducted among hospitalised stroke survivors. Socio-demographic data were collected. Oral clinical assessment (dental plaque scores) and functional dependency levels scores were carried out. Gingival Crevicular Fluids were collected, using absorbent papers and analysed using ELISA kit. Descriptive statistic and correlation analyses were performed using proportion and Spearmen correlation coefficient test. Results: A total of 53 patients were recruited from five public hospitals. There was a significant correlation between CRP and IL-6 levels of GCF (P=0.021, r=0.21). A significant correlation was also observed between CRP levels in GCF with dental plaque scores and functional dependency levels. There was no statistically significant correlation found between IL-6 levels in GCF with dental plaque scores and functional dependency levels. Dental plaque scores were associated with high levels of CRP in GCF (P=0.014), and swallowing problem was associated with high levels of IL-6 in GCF (P=0.002). Conclusions: IL-6 levels in GCF were correlated with the levels of CRP in GCF. High CRP and IL-6 levels in GCF were significantly associated with dental plaque scores and swallowing condition (presence of dysphagia), respectively. Thus, this pilot study suggests that CRP level in the oral cavity respond to the oral health conditions and may not be a predictor factor of stroke outcomes. Further studies are warranted to compare the level of inflammatory biomarkers from the oral cavity and serum in relation to the stroke conditions and outcomes